Effect of Eucalyptus Plantation on Moisture Extraction Pattern, Water Use and Yield of Wheat - Singh, Ajit; Singh, Raj; Pannu, R. K. (Indian Journal of Agroforestry, 2020)
A field experiment was conducted for two crop seasons (1999-2000 and 2000-2001) at research farm of CCS, HAU, Hisar to study the effect of Eucalyptus plantation on moisture extraction pattern, water use and yield of wheat crop. The results indicated that the soil moisture content (SMC) was decreased maximum in S24 and was higher with increase in shade level after each irrigation throughout the crop season. The differences in SMC among different shade levels were higher in advanced stage of the crop. The soil water use (SWU) increased consistently with the advancement of crop and was faster in S24. The variation in percent soil moisture extraction patters (PSME) was highest in S24 than other shade levels and minimum in S6. The PSME on the basis of cm/cm soil depth was maximum from the surface layers and it decreased consistently with increase in profile depth. Among the yield attributes the effect of shade was maximum on effective tillers/ plant and it was minimum on test weight. The yield attributes and grain yield of wheat decreased significantly with successive increase in shade level from S24 and S6 during both the years except effective tillers per plant and test weight between S12 and S18.. The quantum of decrease in grain yield with increased shade was 44.6 %, 21.2 %, 10.8 % and 50.9 %, 29.5 %, 9.6 % during 1999-2000 and 2000-2001, respectively. The reduction in water use efficiency was more than SWU with the increased shade stress.